(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate organic fertilizers in the production of dry matter and accumulation of macronutrients in jambu plants. The experiments were carried out at the Experimental Farm of São Manuel, SP, belonging to the School of Agriculture (FCA) - UNESP and on the Zodiac site, located in the Demétria neighborhood, municipality of Botucatu, SP. Six treatments were evaluated, covering fertilizers, namely ferticel, provaso®, castor bean cake, bokashi, hull flour and horn and a witness without coverage, in five repetitions, using a randomized block design. Dry matter mass and macronutrient accumulation in the inflorescences, vegetative part and aerial part (inflorescences + vegetative part) were evaluated in two harvests in each area. Regarding the dry matter mass, the hull and horn fertilizer resulted in higher values, 444.5, 322.5 m-2; 1286.8, 540 m-2; and 1730.8 and 860 m-2 of accumulation in the inflorescences, vegetative and aerial parts, at the zodiac site and on the São Manuel farm, respectively. The decreasing order of nutrient accumulation (g m-2) in the aerial part of the plants at the Zodiac site was: K (54.37) > N (27.2) > Ca (7.4) > Mg (5.9) > P (4.8) > S (4.6), while at Fazenda São Manuel it was K (23.25) > N (11.4) > Ca (5.3) > P (3.5) > Mg (2.3) > S (1.7).